2023
DOI: 10.1172/jci164118
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency in the omega-3 lysolipid transporter Mfsd2a leads to aberrant oligodendrocyte lineage development and hypomyelination

Abstract: Patients with autosomal recessive microcephaly 15 caused by deficiency in the sodium-dependent lysophosphatidylcholine (LPC) transporter major facilitator superfamily domain–containing 2a (Mfsd2a) present with both microcephaly and hypomyelination, suggesting an important role for LPC uptake by oligodendrocytes in the process of myelination. Here we demonstrate that Mfsd2a is specifically expressed in oligodendrocyte precursor cells (OPCs) and is critical for oligodendrocyte development. Single-cell sequencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Recent work has shown that circulating LPCs are inversely associated with BMI 44 45 , inflammatory markers including C-reactive protein 45 46 and cardiovascular disease risk 45 . Importantly, transport of polyunsaturated LPCs across the blood brain barrier is essential for brain development and myelin synthesis 47 48 . iCR decreased levels of HexCer and LacCer in iCR compared to control groups may reflect an overall reduction in sphingolipid synthesis associated with improved metabolic health, since these sphingolipids have been associated with increased cardiovascular risk in some 49 , but not all studies 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has shown that circulating LPCs are inversely associated with BMI 44 45 , inflammatory markers including C-reactive protein 45 46 and cardiovascular disease risk 45 . Importantly, transport of polyunsaturated LPCs across the blood brain barrier is essential for brain development and myelin synthesis 47 48 . iCR decreased levels of HexCer and LacCer in iCR compared to control groups may reflect an overall reduction in sphingolipid synthesis associated with improved metabolic health, since these sphingolipids have been associated with increased cardiovascular risk in some 49 , but not all studies 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, new structural data indicate that the Na + binding site is near the phospholipid headgroup and may act to stabilize the molecule rather than be co-transported across the plasma membrane [23]. Mice deficient in MFSD2a have severe microcephaly, brain DHA deficiency, and learning and memory deficits [18]. Additional support for an important role for MFSD2a in normal brain growth and development include studies of human non-lethal inactivating mutations in MFSD2a, which result in microcephaly, due to reduced white matter volume, and intellectual disability [24].…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, Nguyen and coworkers reported that Major Facilitator Superfamily domaincontaining 2a (MFSD2a) is expressed in the endothelial cells of the blood-brain barrier and provided evidence that it transports DHA in the form of lysophosphatidylcholine (LPC-DHA) [17]. Mice deficient in MFSD2a have severe microcephaly, brain DHA deficiency, and learning and memory deficits [18]. The role of placental MFSD2a in the delivery of DHA to the fetal brain is currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the brain tissue contains high levels of Omega-3 PUFAs and Omega-6 PUFAs, which play signi cant roles in various biological processes such as metabolism, neurotransmission, synaptogenesis, and in ammation [12,13]. Some studies suggest that ADHD is linked to changes in the levels and functionality of UFAs in the brain [14,15], while other studies contradict these ndings [16].…”
Section: Introductionmentioning
confidence: 99%